Simple simultaneous determination of butylated hydroquinone (TBHQ) and butylated hydroxyanisole (BHA) antioxidants in oil using high‐performance liquid chromatography with chemiluminescence detection. (10th April 2014) - Xu, Shuangjiao; Chen, Funan; Deng, Mao; Sui, Yanyan
ABSTRACT A highly sensitive and convenient high‐performance liquid chromatography technique coupled with chemiluminescence detection for the simultaneous determination butylated hydroquinone (TBHQ) and butylated hydroxyanisole (BHA) in oil is established. The detection is based on the inhibitory effect on the CL reaction between luminol and potassium ferricyanide in an alkaline medium. Samples were separated through a reverse‐phase C18 column using a mobile phase of methanol and water (80: 20, v/v) at a flow rate of 0.5 mL/min. The effects of various parameters including mobile phase, flow rate and chemiluminescence regent were studied. Under optimum conditions, both TBHQ and BHA showed good linear relationships in the range 1 × 10‐7–1 × 10‐5 g/mL with detection limits of 24 and 33 ng/mL, respectively. The proposed method is simple and sensitive, with low costs. The method was successfully applied for the quantification of TBHQ and BHA in sesame oil. The possible inhibition mechanism is also discussed briefly. Copyright © 2014 John Wiley & Sons, Ltd.